2012
DOI: 10.1245/s10434-012-2623-9
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Metastasis Is Associated with Retroperitoneal Lymph Node Relapses in Women Treated for Colorectal Peritoneal Carcinomatosis

Abstract: Retroperitoneal lymph node recurrence seems to be linked to OM originating from colorectal cancer and could worsen the prognosis. A systematic lymphadenectomy could be evaluated in women with isolated OM or very limited peritoneal carcinomatosis to analyze the incidence of invaded lymph nodes and study its potential benefit on survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Two previous studies have investigated the outcomes of CRS and HIPEC in patients with, and without, ovarian metastases, although in both studies the majority, or all, of the study population had colorectal peritoneal metastases [24,25]. In addition, the study population of 405 patients in the current study exceeds that of the other studies (105 and 125 patients, respectively).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Two previous studies have investigated the outcomes of CRS and HIPEC in patients with, and without, ovarian metastases, although in both studies the majority, or all, of the study population had colorectal peritoneal metastases [24,25]. In addition, the study population of 405 patients in the current study exceeds that of the other studies (105 and 125 patients, respectively).…”
Section: Discussionmentioning
confidence: 81%
“…The extent of peritoneal disease was graded using the peritoneal cancer index (PCI), which ranges from 0 to 39 [13]. The median PCI was 18 (interquartile range, IQR, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Median follow-up was 40 months (IQR 27-59).…”
Section: Study Populationmentioning
confidence: 99%
“…Cytoreductive surgery (CRS) for KTs carries a significant locoregional or metastatic recurrence rate despite achieving an initial R0 resection. KTs in particular have been linked to retroperitoneal lymph node recurrence [8] . It has been suggested that should KT be discovered incidentally upon resection of a colorectal primary, systematic second-look surgery should be performed to exclude peritoneal metastasis [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Peng et al reported that gastrectomy and absence of ascites were the two independent prognostic factors associated with longer survival in gastric cancer (16). In addition, for colorectal cancer with peritoneal metastases, the presence of ovarian metastases did not affect prognosis in patients undergoing complete cytoreductive surgery with IP chemotherapy (17). Removing microscopic residual tumor is the expected effect of the surgery.…”
Section: Discussionmentioning
confidence: 99%